PENGARUH KARAKTERISTIK INDIVIDU DAN KARAKTERISTIK PEKERJAAN TERHADAP LOYALITAS KARYAWAN DI PT. BUMA CIMA NUSANTARA UNIT CINTA MANIS - Sudarta, Sudarta; Areni, Areni (Bussman Journal : Indonesian Journal of Business and Management, 2023)
This research was conducted with the aim of knowing the effect of individual characteristics and job characteristics jointly and partially on employee loyalty at PT. Buma Cima Nusantara Unit Cinta Manis. This type of research is associative. The sample used was 68 employees at PT. Buma Cima Nusantara Unit Cinta Manis with sampling technique using purposive sampling. The data used in this study are primary data. The data collection method used was through questionnaires and documentation. The data analysis technique used is Multiple Linear Regression Analysis Technique, F test, t test, and the coefficient of determination. The results of this study based on multiple linear regression indicate that individual characteristics and job characteristics have a positive effect on employee loyalty at PT. Buma Cima Nusantara Unit Cinta Manis. The results of simultaneous hypothesis testing indicate that there is a significant effect of individual characteristics and job characteristics on employee loyalty at PT. Buma Cima Nusantara Unit Cinta Manis. The results of the t test show that there is a significant effect of individual characteristics or job characteristics partially on employee loyalty at PT. Buma Cima Nusantara Unit Cinta Manis. The results of the coefficient of determination indicate that the contribution of changes in individual characteristics and job characteristics is 15.6%. While the remaining 84.4% was contributed by other variables not included in this study